Linked heat treatment and bending simulation of aluminium tailored heat treated profiles - Froeck, Hannes; Graser, Matthias; Reich, Michael; Lechner, Michael; Merklein, Marion; Kessler, Olaf (Minerals, Metals and Materials Series, 2017)
Precipitation hardening aluminium alloys enable tailoring of mechanical properties through the dissolution of strength-increasing precipitates during a local short-term heat treatment. Tailor Heat Treated Profiles (THTP) are aluminium extrusion profiles with locally different material properties, specifically optimised for succeeding bending processes. Softened areas need to be generated next to hardened areas to optimise the material flow during the forming process. To determine the optimised layout of softened and hardened areas, a process chain simulation consisting of the simulation of the short-term heat treatment and the subsequent forming process seems purposeful. The numerical modelling of short-term heat treatment requires a coupled computation of thermal and mechanical simulation with particular focus on the evaluation of microstructure and consequently on the change of mechanical properties. The dissolution and precipitation behaviour during heating and cooling of aluminium profiles 6060 T4 is investigated using differential scanning calorimetry. Thermo-mechanical analysis is applied for evaluation of the mechanical properties. This behaviour should be described in a material model with the software LS DYNA. The heat treatment simulation provides a distribution of mechanical properties along the profile, which is an important input parameter for the following forming simulation. In order to avoid a loss of information between the heat treatment simulation and forming simulation, both linked simulations are performed with the software LS DYNA.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Aluminium alloy; Differential scanning calorimetry; EN AW-6060; Tailor heat treated profiles (THTP)